Chemical and microstructural characterisation of HfO2-Y2O3 ceramics with high amount of Y2O3 (33, 40 and 50 mol. %) manufactured using spark plasma sintering. Issue 5 (May 2023) - Audouard, L.; Tsoutsouva, M.G.; Horezan, N.; Rimpot, E.; Justin, J.F.; Bertrand, P.; Langlade, C.; Garcia, M.; Julian-Jankowiak, A.
Abstract: Hafnia based ceramics are potential promising candidates to be used as thermal barrier coatings (TBC) for applications in the field of propulsion. In this study, Spark Plasma Sintering (SPS) of fully stabilised hafnia with yttrium oxide (yttria) was investigated to provide a better understanding of the effect of manufacturing parameters, on the crystallography, chemistry and microstructure of the material. Several hafnia powders, containing different amounts of yttria (33 mol. %, 40 mol. % or 50 mol. %), were sintered by SPS at different temperature levels ranging from 1600 °C to 1850 °C. On these materials, X-ray diffraction patterns associated with scanning electron micrographs have highlighted the influence of both the sintering temperature and the amount of yttria on the final composition, the lattice parameter and the microstructure of hafnia-based materials. In the end, it is established that, for all quantities of yttrium employed, the main phase is Y2 Hf2 O7 with very high densification levels. Highlights: Obtention of fully dense HfO2 -Y2O3 ceramics considering very high amounts of Y2 O3 and using Spark Plasma Sintering. Promotion of the formation of the Y2 Hf2 O7 phase by increasing the sintering temperature and decreasing the amount of Y2 O3 . Chemical homogeneity is improved for temperatures higher than 1800 °C and for 33 mol. % of Y2 O3 .